Combined effects of smoking and HIV infection on the occurrence of aging-related manifestations - Laurent Boyer; Sonia Zebachi; Sébastien Gallien; Laurent Margarit; Bruno Ribeiro Baptista; José-Luis Lopez-Zaragoza; Thomas D’Humières; Françoise Zerah; Sophie Hue; Geneviève Derumeaux; Serge Adnot; Etienne Audureau; et al. (Scientific Reports, 2023)
Abstract Both HIV-1 infection and smoking may contribute to the development of ageing-related manifestations affecting the prognosis of people living with HIV, but it is unclear whether HIV and smoking exert their effects independently or interact by potentiating each other. We conducted a cross-sectional study in 192 people living with HIV aged- and gender-matched with 192 HIV-uninfected controls, assessing the relative effect of HIV-1/smoking status on lung function (FEV1), bone mineral density (BMD), appendicular skeletal muscle mass index (ASMI), aortic pulse-wave velocity (PWV), insulin resistance (HOMA-IR) and renal function. In both unadjusted and adjusted analyses, FEV1, BMD and ASMI significantly differed according to smoking/HIV status, with the worst parameters found in HIV-1 infected patients currently smoking, and BMD and ASMI decreased to a lesser extent in HIV-1 infected patients formerly smoking (> 10 pack-years). Values in people living with HIV with < 10 pack-years exposure were of similar magnitude to those from controls. Regarding PWV, HOMA-R and eGFR, no significant differences were found, with the exception of eGFR values which were globally lower in HIV-1 infected patients. In conclusion HIV infection and smoking acted synergistically and were associated with a wasting phenotype combining muscle mass and bone mineral reduction. Clinical Trial Registration (registrar, website, and registration number), where applicable: CPP 10-023, 09-027, 10-034.